Impact of Age on Outcomes in Patients With Cardiogenic Shock - Kanwar, Manreet; Thayer, Katherine L.; Garan, Arthur Reshad; Hernandez-Montfort, Jaime; Whitehead, Evan; Mahr, Claudius; Sinha, Shashank S.; Vorovich, Esther; Harwani, Neil M.; Zweck, Elric; Abraham, Jacob; Burkhoff, Daniel; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Advanced age is associated with poor outcomes in cardiovascular emergencies. We sought to determine the association of age, use of support devices and shock severity on mortality in cardiogenic shock (CS). Methods: Characteristics and outcomes in CS patients included in the Cardiogenic Shock Work Group (CSWG) registry from 8 US sites between 2016 and 2019 were retrospectively reviewed. Patients were subdivided by age into quintiles and Society for Cardiovascular Angiography & Interventions (SCAI) shock severity. Results: We reviewed 1,412 CS patients with a mean age of 59.9 ± 14.8 years, including 273 patients > 73 years of age. Older patients had significantly higher comorbidity burden including diabetes, hypertension and coronary artery disease. Veno-arterial extracorporeal membrane oxygenation was used in 332 (23%) patients, Impella in 410 (29%) and intra-aortic balloon pump in 770 (54%) patients. Overall in-hospital survival was 69%, which incrementally decreased with advancing age (p < 0.001). Higher age was associated with higher mortality across all SCAI stages (p = 0.003 for SCAI stage C; p < 0.001 for SCAI stage D; p = 0.005 for SCAI stage E), regardless of etiology (p < 0.001). Conclusion: Increasing age is associated with higher in-hospital mortality in CS across all stages of shock severity. Hence, in addition to other comorbidities, increasing age should be prioritized during patient selection for device support in CS.